MOTHER KNOWLEDGE ABOUT FEEDING TO TODDLERS TO PREVENT STUNTING AT THE SIDOARJO HEALTH CENTER SIDOARJO DISTRICT - Sri Hardi Wuryaningsih; Siswari Yuniarti; Nathacia Vicky Putri Hermawan (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2024)
Introduction: Nutritional problems in general consist of deficiency and excess nutrition. Malnutrition in children, especially toddlers, are still a problem in Indonesia. One of them is stunting, stunting is a condition in which children experience growth disorders, so that the child's height does note match his age, US a result of chronic nutritional problems. One of the causes of stunting is the lack of knowledge of mothers in fulfilling conditions child nutrition. The purpose of this study was to identify mothers' knowledge about feeding toddlers to prevent stunting. Methods: This type of research is descriptive. The population of this study were mothers who had children aged 1-5 years as many as 91 people. The technique used to take samples is accidental sampling. Data collection used a questionnaire and then analyzed using frequency distribution and percentage. Results and Analysis: The results of this study indicates that most mothers of toddlers are knowledgeable enough. Knowledge of mothers of toddlers aged 35 years, mothers of toddlers aged 20-35 years, and mothers of toddlers aged <20 years are mostly knowledgeable enough. Knowledge of toddlers mothers in terms of the education of all toddler mothers with elementary - junior high school education, and a small number of toddler mother with high school education have less knowledge. Knowledge of mother of toddler in terms of the work of most of the mother who work are knowledgeable enough. Discussion: It is hoping that mothers of toddlers will seek information about feeding toddlers to prevent stunting through health workers, print and electronics media, listen when health education is given and apply it in everyday life US an effort to minimize the risk of stunting.